You Have to be Stupid to See That - Žižek, Slavoj (Stasis, 2018)
The article presents a philosophical analysis of a current historical situation, in which humanity is facing the urgency of a radical politicoeconomic change, a need to establish a new mode of relating to our environs, which can be understood as civilizing civilizations, or imposing universal solidarity and cooperation among all human communities. This task is rendered all the more difficult by both the ongoing rise of sectarian fundamentalist violence, and its (apparent) opposite, that is, cynical indifference. Addressing Marx’s well-known characterization of religion as the “opium of the people,” this article shows, using the most real examples of our social and political reality, how ideology functions and how it affects our ideas of equality and freedom.